2021
DOI: 10.1159/000520574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prodromal Presentations of Parkinson’s Disease among Primary Care Outpatients in Germany

Abstract: Background: This study aimed to identify clinical features that predate the diagnosis of PD in a primary care setting. Methods: This retrospective case-control study was based on data from the Disease Analyzer database (IQVIA) and included 17,702 patients with Parkinson’s disease and 17,702 non-PD controls matched for age, sex, and index year. We analyzed the prevalence of 15 defined diagnoses and symptoms documented within 2 years, ≥2 to <5, and ≥5 to <10 years prior to the index date in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
(37 reference statements)
1
10
2
Order By: Relevance
“…These findings confirm the prominent autonomic involvement in the early stages of MSA, including postural hypotension, constipation, and urinary dysfunction, with early and prominent balance problems and a proportion who have ataxia. Compared to our results in Parkinson's disease study in the same database (11), the differences in the ORs regarding hypotension (OR 15.69 vs 2.28), balance impairments (OR 11.23 vs 3.47), and urinary dysfunction (OR 4.49 vs 2.64) in the 2 years before diagnosis are particularly noticeable.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…These findings confirm the prominent autonomic involvement in the early stages of MSA, including postural hypotension, constipation, and urinary dysfunction, with early and prominent balance problems and a proportion who have ataxia. Compared to our results in Parkinson's disease study in the same database (11), the differences in the ORs regarding hypotension (OR 15.69 vs 2.28), balance impairments (OR 11.23 vs 3.47), and urinary dysfunction (OR 4.49 vs 2.64) in the 2 years before diagnosis are particularly noticeable.…”
Section: Discussioncontrasting
confidence: 89%
“…A pattern of initial genitourinary dysfunction followed by orthostatic hypotension and sleep disorders including RBD and sleep apnoea, and respiratory disturbances including excessive snoring and stridor has been suggested [4,6]). Olfactory loss and cognitive impairment [3,6,8,9] on the other hand have been suggested to be relatively rare in the early phase of MSA, unlike in PD where these are reported to be early complaints [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that tremor may be an early feature of PD. 9,[32][33][34] In people reporting tremor years before diagnosis, one must consider the possibility that diagnosis is simply delayed in primary care. That is, individuals seeing general practitioners may not be referred early enough to a movement disorders specialist.…”
Section: Discussionmentioning
confidence: 99%
“…This extends and confirms our previously reported analysis of some of the included risk factors and prodromal features of PD in the German specialist practices. 2 This study also had limitations, as it relied on diagnosis of PD using patient medical records, and application of diagnostic criteria was not possible. Although other electronic health care databases, such as The Health Improvement Network in the UK, have shown acceptable accuracy of primary care diagnosis of PD using a single diagnostic code, 1 albeit with slightly higher incidence rates, 72 no validation study is available in this data source.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…rodromal features of Parkinson disease (PD) can start more than a decade before the typical clinical symptoms allow a diagnosis. 1,2 In addition, there is increasing evidence for a number of possible risk factors that may predispose to the manifestation of the disease or facilitate development or spread of pathological lesions. These risk factors include well-known genetic or environmental risk factors but also diabetes type 2 or gastric pathology, which may increase spread of pathology from the enteric nervous system via the vagal nerve to the central nervous system.…”
mentioning
confidence: 99%